Subclinical hypothyroidism, depression and cognitive impairment: experience at a Lambayeque elderly center - Gonzales Gonzales, Carol (2014)
Introduction: There are few studies on subclinical hypothyroidism in the elderly. Objectives: To determine the frequency of subclinical hypothyroidism, depression and cognitive impairment, and explore their association in elderly patients. Design: Descriptive, crosssectional study. Scenario: EsSalud seniors’ center, Lambayeque, Peru. Methods: In 2012 and 2014 TSH and T4L were determined by ELISA in 84 elderly patients. Depression was assessed through a reduced Yesavage test and cognitive impairment by the mini mental test. Frequencies and percentages were determined and prevalence ratios with 95% confidence intervals were estimated using Epidat v3.1. Main outcome measures: Subclinical hypothyroidism, depression and cognitive impairment and their association. Results: Sixtyfive women (77%) and 19 men (23%) were included. Subclinical hypothyroidism was found in 11 older adults (13.1%), depression in 36 (42.9%) and cognitive impairment in 11 (13.1%). No association between subclinical hypothyroidism and depression (PR: 0.85, CI95% [0.39-1.85], p: 0.677) or subclinical hypothyroidism and cognitive impairment (RP: 2.48, CI95% [0.77-7.98], p: 0.1349) were found. Conclusions: There was a high frequency of subclinical hypothyroidism, depression, and cognitive impairment in the elderlies studied. There was no association between subclinical hypothyroidism and depression or cognitive impairment.